Selenate and selenite transporters in proso millet: Genome extensive detection and expression studies under salt stress and selenium - Mushtaq, Naveed Ul; Alghamdi, Khalid M.; Saleem, Seerat; Shajar, Faamiya; Tahir, Inayatullah; Bahieldin, Ahmad; Rehman, Reiaz Ul; Hakeem, Khalid Rehman (Frontiers in Plant Science, 2022)
Crops are susceptible to a variety of stresses and amongst them salinity of soil is a global agronomic challenge that has a detrimental influence on crop yields, thus posing a severe danger to our food security. Therefore, it becomes imperative to examine how plants respond to salt stress, develop a tolerance that allows them to live through higher salt concentrations and choose species that can endure salt stress. From the perspective of food, security millets can be substituted to avoid hardships because of their efficiency in dealing with salt stress. Besides, this problem can also be tackled by using beneficial exogenous elements. Selenium (Se) which exists as selenate or selenite is one such cardinal element that has been reported to alleviate salt stress. The present study aimed for identification of selenate and selenite transporters in proso millet (Panicum miliaceum L.), their expression under NaCl (salt stress) and Na2SeO3 (sodium selenite) treatments. This study identified eight transporters (RLM65282.1, RLN42222.1, RLN18407.1, RLM74477.1, RLN41904.1, RLN17428.1, RLN17268.1, RLM65753.1) that have a potential role in Se uptake in proso millet. We analyzed physicochemical properties, conserved structures, sub-cellular locations, chromosome location, molecular phylogenetic analysis, promoter regions prediction, protein-protein interactions, three-dimensional structure modelling and evaluation of these transporters. The analysis revealed the chromosome location and the number of amino acids present in these transporters as RLM65282.1 (16/646); RLN42222.1 (1/543); RLN18407.1 (2/483); RLM74477.1 (15/474); RLN41904.1 (1/521); RLN17428.1 (2/522); RLN17268.1(2/537); RLM65753.1 (16/539). The sub-cellular locations revealed that all the selenite transporters are located in plasma membrane whereas among selenate transporters RLM65282.1 and RLM74477.1 are located in mitochondria and RLN42222.1 and RLN18407.1 in chloroplast. The transcriptomic studies revealed that NaCl stress decreased the expression of both selenate and selenite transporters in proso millet and the applications of exogenous 1µM Se (Na2SeO3) increased the expression of these Se transporter genes. It was also revealed that selenate shows similar behaviour as sulfate, while selenite transport resembles phosphate. Thus, it can be concluded that phosphate and sulphate transporters in millets are responsible for Se uptake. .